The use of progressives among Malaysian ESL learners. - Narinasamy, Ilhamanggai; Mukundan, Jayakaran; Nimehchisalem, Vahid (Canadian Center of Science and Education, 2013)

(untitled)
Studies on ESL/EFL learners’ use of the progressives reveal that it is one of the grammatical aspects most problematic to them. This paper presents the results of a study on the use of progressives among Year 5, Form 1 and Form 4 Malaysian ESL learners’ compositions using the English of Malaysian School Students (EMAS) corpus. The purpose of this study is to investigate if the progressives do pose any difficulties to Malaysian ESL learners. The results showed that the use of progressives increase in frequency in tandem with the educational levels of the ESL learners, indicating there is an ongoing development in language learnt. The frequency count of progressives in the ‘Picture-Based’ essay was higher by 74.25% compared to ‘The Happiest Day of My Life’ essay. It was also found that the past progressives were used more than the present progressives across levels. These findings might be connected to the genre of the essays written. The findings may have useful implications for English language teachers in preparation to teach the progressives more effectively; syllabus designers to look into efficient ways to incorporate progressives into the curriculum; and material developers to produce helpful resources in aiding language teachers’ attempts in explaining this troublesome grammar construction.